Hybrid synthesis of zirconium oxycarbide nanopowders with defined and controlled composition. Issue 6 (23rd January 2019) - Hauser, Daniel; Auer, Andrea; Kunze-Liebhäuser, Julia; Schwarz, Sabine; Bernardi, Johannes; Penner, Simon
Abstract : A combined synthesis strategy involving a carbothermal reduction and gelation approach with glycine as gelating agent was used to obtain Zr-based (oxy)carbide materials with defined and controlled composition. Abstract : A combined synthesis strategy involving a carbothermal reduction and gelation approach with glycine as gelating agent was used to obtain Zr-based (oxy)carbide materials with defined and controlled composition. A comparatively low temperature approach (1500 °C) allows exploration of the ZrC–ZrO2 phase diagram and reproducibly leads to zirconium (oxy)carbide phases with different C/Zr ratios, as confirmed by combined X-ray diffraction (XRD) and transmission electron microscopy (TEM) data. The latter also indicates a chemically very homogeneous distribution of oxygen and carbon throughout the sample bulk, a prerequisite for further characterization of its intrinsic physico-chemical properties. Due to the general variability of the synthesis procedure – variation of metal precursor, amount of gelating agent and carbon precursor source – it is expected that the method can be easily adapted and transferred to other metal – oxycarbide materials.